P- and S-Wave Velocity Structures and the Influence of Volcanic Activities in the East Java Area From Seismic Tomography - Syawaldin Ridha; Sukir Maryanto; Agustya A. Martha; Vanisa Syahra; Muhajir Anshori; Pepen Supendi; Sri Widiyantoro; Sri D. Wuryani; Rendi P. Hab Sari (International Journal of Geophysics)
The tectonic complexity in Indonesia has made it one of the most interesting targets for studies on seismic tomography. The Indian oceanic plate sunk beneath the Eurasian continental plate, forming the subduction zone in Southern Indonesia. This activity led to the formation of volcanoes along the Sunda Arc, including East Java, the research area covered in this study. This research is mainly aimed at identifying the influence of the volcanic activities by tomography analysis. The data of the earthquakes was recorded by 22 seismic stations of the Indonesia Tsunami Early Warning System (InaTEWS) seismic network in the period of 2009–2017. The tomographic image was analysed by exploring the anomalies of primary (P)- and secondary (S)-wave velocities and Vp/Vs ratio. The result shows the presence of a low-velocity zone with a high Vp/Vs ratio found around the volcanic area, which is correlated with the partial melting zone or magma chamber. The low-velocity zone was observed at the depth range of 27–155 km, which was also correlated with the subducted slab beneath Java Island. This leads to an assumption that there is an interlinked volcanic system which extends from west to east of Java.